Occipital encephalocele in a neonate: a case successfully managed by excision and formation of a reverse visor scalp flap. Issue 1 (21st January 2020) - Tan, Elizabeth; Makaranka, Stanislau; Mohamed, Nusrat; Cavale, Naveen
Abstract : Encephaloceles are one form of neural tube defect and are associated with partial absence of skull bone fusion, with an incidence of 1–4 cases for every 10 000 live births. We report the case of a neonate born at term, with an antenatal diagnosis of occipital encephalocele, which was successfully managed with excision and formation of a reverse visor scalp flap on day 2 of life. Surgery was performed in a single stage, involving a multidisciplinary approach between neurosurgery and plastic surgery teams, with wider management involving neonatal intensive care, paediatric, obstetric and anaesthetic teams. The patient had no early postoperative complications, and we use this case report to demonstrate that a reverse visor scalp flap is a good option to cover full-thickness defects in patients with encephaloceles. Furthermore, we advocate early repair and a multidisciplinary approach to minimise the morbidity associated with occipital encephaloceles.